Role Wii Fit exer-games in improving balance confidence and quality of life in elderly population - Kiran Khushnood; Shafaq Altaf; Nasir Sultan; Malik Muhammad Ali Awan; Riafat Mehmood; Sidra Qureshi (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effects of Wii Fit exer-gaming on balance confidence, quality of life and fall risk in elderly population Methods: A double blinded randomized control was conducted at Kulsum International Hospital, Islamabad from July 31st to October 30th, 2018. Following screening, 90 subjects fulfilled inclusion criteria and gave consent to be part of trial. Subjects were randomly allocated into experimental and control group by concealed envelope method. After baseline assessment, experimental group received Wii fit gaming while controls received balance training for 30 minutes twice a week for 8 weeks. Activities balance confidence (ABC), Euro 5Q5L, timed up and go (TUG) and Fukuda were used as outcome measures. Data was analysed by SPSS 21. Results: ABC improved in experimental group from 76.47±3.69 to 86.53±3.99, and in control group from 77.51±3.01 to 82.70±2.78 with significance < 0.001. The components of Euro 5Q5L; mobility, self-care, usual activities, pain/discomfort, anxiety/depression have changed with intergroup significance of 0.05, 0.006, 0.595, <0.001, 0.001 respectively. TUG and Fukuda improved in experimental and control group as 15.73±2.30 to 12.02±1.40 and 16.24±1.75 to 13.68±1.58 with significance <0.001, and from 41.78±6.to 71 to 30.09±8.05 and 43.36±5.59 to 38.68±5.75 with significance <0.001 respectively. Conclusion: Wii fit improves balance confidence and quality of life reducing fall risk in elderly. Clinical Trial Number: IRCT20180417039344N1 Keywords: Balance training, Elderly, Exer-gaming, Quality of life, Wii fit Continuous...